2022
DOI: 10.1186/s12302-022-00597-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of wastewater treatment plants on microbiological contamination for evaluating the risks of wastewater reuse

Abstract: Background Wastewater reuse represents a promising alternative source of water supply considering the water scarcity related to climate change. However, if not adequately treated, wastewater represents a source of microbiological health risk. The purpose of this work was to investigate the role of wastewater treatment on microbiological contamination by evaluating the possible risks associated with wastewater effluent reuse, taking into account new EU legislation (2020/741) on minimum requireme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 32 publications
0
7
0
2
Order By: Relevance
“…S. Bonetta et al (7) emphasise the fact that even in the case of a perfect wastewater treatment system, including biological treatment, all dissolved inorganic substances and about 10% of organic pollutants remain in the treated wastewater. According to the authors, this indicates the need for a radical reorientation of the water use strategy, with the isolation of the anthropogenic water cycle from the natural one, transition to closed water supply, and introduction of low-waste technologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. Bonetta et al (7) emphasise the fact that even in the case of a perfect wastewater treatment system, including biological treatment, all dissolved inorganic substances and about 10% of organic pollutants remain in the treated wastewater. According to the authors, this indicates the need for a radical reorientation of the water use strategy, with the isolation of the anthropogenic water cycle from the natural one, transition to closed water supply, and introduction of low-waste technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Scientists of Kyrgyzstan pay special attention to the toxic and carcinogenic properties of some components of wastewater from industry and municipal services (4)(5)(6) . Modern scientists S. Bonetta et al (7,8) and H. Hamdhani et al (9) come to the conviction that many destructive changes in aquatic ecosystems, difficult to regenerate, are provoked by large-scale releases of toxic substances from industrial processes. The conclusions of scientists are complemented by a group of researchers led by S. Lu et al (10) and M. Preisner (11) are convinced of the special urgency of the impact on natural reservoirs of new understudied pollutants, which actually cannot be treated even with satisfactory condition of complete wastewater treatment systems.…”
Section: Introductionmentioning
confidence: 99%
“…2). E. coli and TC concentrations are supposed to be strictly dependent on several factors such as the intrinsic characteristic of the wastewater treatment plant (e.g., activated sludge, membrane bioreactor) and, when applied, to the disinfection system adopted (e.g., PPA, hypochlorite, UV) (Bonetta et al, 2022). Indeed, Perulli et al (2021), found E. coli and TC, 1000 and 100 times reduced in a wastewater deriving from a different treatment plant.…”
Section: Wastewater Microbiological Qualitymentioning
confidence: 99%
“…Существующие технологии зачастую многостадийны, весьма затратны, требуют применения большого количества химических реагентов, что приводит к вторичному загрязнению окружающей среды. Можно констатировать, что эта проблема актуальна для промышленности всего мира, поэтому исследования проводятся во всех странах [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionunclassified